2014
DOI: 10.7314/apjcp.2014.15.11.4677
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Lymph Node Pathology in Western Saudi Arabia

Abstract: Background: This study aimed to characterize the histopathological pattern of lymph node pathology among Saudi patients and to highlight the age and gender variations of these lesions as base line data. Materials and Methods: We retrospectively analyzed the data from lymph node biopsy specimens received at the Department of Pathology, King Fahad Hospital, Madinah, Saudi Arabia from January 2006 to December 2013. Results: Of the 289 lymph node biopsy specimens received, 154 (53.3%) were from males and 135 (46.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(22 reference statements)
2
4
0
Order By: Relevance
“…It may be due to inclusion of only adult patient in our study. In this present series a total of 70 patient underwent lymph node Biopsy and it was observed that 30.0% patients had lymphoma, in our country Miah [1] showed lymphoma cases were (28%), another study done in Saudi Arabia by Albasri et al, [16] which shows number of lymphoma were 24.6% which is similar to our study and according to Olu-Eddo & Ohanaka [17] lymphoma cases were 23%. In this series the second leading cause of lymphadenopathy were nonspecific lymphadenopathy (25.7%), In India Mohan et al, [18] showed nonspecific lymphadenitis cases were 35.6%.…”
Section: Discussionsupporting
confidence: 89%
“…It may be due to inclusion of only adult patient in our study. In this present series a total of 70 patient underwent lymph node Biopsy and it was observed that 30.0% patients had lymphoma, in our country Miah [1] showed lymphoma cases were (28%), another study done in Saudi Arabia by Albasri et al, [16] which shows number of lymphoma were 24.6% which is similar to our study and according to Olu-Eddo & Ohanaka [17] lymphoma cases were 23%. In this series the second leading cause of lymphadenopathy were nonspecific lymphadenopathy (25.7%), In India Mohan et al, [18] showed nonspecific lymphadenitis cases were 35.6%.…”
Section: Discussionsupporting
confidence: 89%
“…The spectrum of conditions causing lymphadenopathy was broad and comprised a mixture of infective, malignant, and benign causes similar to findings from case series in Peru 8 and resource-limited settings elsewhere. 9–14 Clinical characteristics were not specific in attaining a diagnosis. TB was given as the most likely diagnosis in the majority of the patients (76%), whereas in fact hyperplasia, lymphoma, and other malignancy each also contributed a significant burden of disease.…”
Section: Discussionmentioning
confidence: 98%
“… 12 - 15 There is however, only one article in the local literature for hospital-based cancer data for Al-Madinah, which was carried out almost 20 years back. 16 Although there has been some very recent hospital-based research publications from Al-Madinah; these articles have reported general disease patterns and cancers in many different organs such as large bowel, 17 , 18 prostate, 19 lymph nodes, 20 and thyroid, 21 but no data is available for this common and important disease, namely BC. We will be investigating this important problem of BC in the rapidly growing and advancing region of Al-Madinah; based on the histopathology diagnosis of biopsies and mastectomies/axillary dissections performed in the local population; and compare our data with previous international and national studies.…”
mentioning
confidence: 99%